2021
DOI: 10.4103/jfmpc.jfmpc_2430_20
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge, and attitude toward venous thromboembolism among Aseer Population, Saudi Arabia

Abstract: Objectives: Calls to carry efforts to increase awareness about venous thromboembolism (VTE) as a preventable major healthcare problem with serious consequences has been upraised. This study was planned to get an overview of the awareness, knowledge, and attitude toward VTE among Aseer population, Saudi Arabia and the need for an education plan. Materials and Methods: Questionnaire composed of 35 questions based cross-sectional study was conducted online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This finding shed light on the vital role of health-care providers in educating their patients about the benefits of ambulating during hospitalization. This finding is in agreement with other studies that were conducted in Jordan, 10 Saudi Arabia, 14,21 and Canada. 13 Another study that was conducted to measure global public awareness of nine countries, including the United States, the United Kingdom, the Netherlands, Thailand, Japan, Germany, Canada, Australia, and Argentina, showed that immobility is the most recognized VTE risk factor in these countries.…”
Section: Discussionsupporting
confidence: 94%
“…This finding shed light on the vital role of health-care providers in educating their patients about the benefits of ambulating during hospitalization. This finding is in agreement with other studies that were conducted in Jordan, 10 Saudi Arabia, 14,21 and Canada. 13 Another study that was conducted to measure global public awareness of nine countries, including the United States, the United Kingdom, the Netherlands, Thailand, Japan, Germany, Canada, Australia, and Argentina, showed that immobility is the most recognized VTE risk factor in these countries.…”
Section: Discussionsupporting
confidence: 94%
“…This observation reinforces the findings of previous studies. [ 2 5 6 7 8 ] While 87.4% of participants self-reported that they were aware of thrombosis, less than half were aware of DVT and PE. In contrast to previous reports, there was no significant difference in the awareness of DVT and PE in the present sample.…”
Section: Discussionmentioning
confidence: 99%
“…The preexisting literature describing public awareness of VTE was reviewed. [ 1 2 3 4 5 6 7 8 ] These data were used to develop a validated questionnaire investigating the knowledge, understanding, and awareness of VTE among the general public throughout Saudi Arabia. To facilitate regional, national, and international comparisons, the questionnaire used in the studies conducted by Wendelboe et al ., 2015,[ 2 ] was modified and translated into Arabic using the Brislin back-translation method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] In 2021, research has been conducted in the Aseer population, Saudi Arabia about VTE awareness and the result was lacking knowledge and satisfaction. [ 15 ] Due to the limited data on public awareness about DVT in the western region of KSA, this study was done to evaluate the knowledge about DVT among KSA western region residents. Our study shows deficient knowledge about VTE among the general population, and this could be corrected by frequent educational programs and awareness promotion campaigns as one of the primary health care canter’s activities guided by primary care physicians.…”
Section: Introductionmentioning
confidence: 99%